Nanoencapsulação de curcumina em polímeros biodegradáveis/biocompatíveis - Buzanello, Rosana Aparecida da Silva (2013)
Curcumin can potencially substitute synthetic dyes considered harmful to human health. However, its susceptibility to external agents and very low water solubility turn its industrial application into a challenge. The nanoencapsulation of curcumin in biocompatible, biodegradable polymers is a promising alternative to enable the use of curcumin. In this work, the miniemulsification/solvent evaporation technique was used to obtain nanoparticles composed by biodegradable/biocompatible polymers (poly(L-lactic acid) (PLLA) and Eudragit S100 (poly(methyl methacrylate-co-methacrylic acid)) containing curcumin. A full factorial experimental design (2k) to four variables was carried to evaluate the Z-average diameter and polydispersity index of PLLA nanoparticles without curcumin. Results demonstrated the existence of complex relationships between the experimental variables and also that the polidispersion index is less sensitive to the change in the experimental conditions than the particles diameter. The methodology for quantification by UV-Vis spectrophotometry was evaluated in respect to the figures of merit: linearity, specificity, accuracy, precision and limits of detection and quantification. Curcumin recovery and the encapsulation efficiency can be safely determined by this methodology. The curcumin nanoencapsulation was studied and the influence of curcumin concentration, type of surfactant and the encapsulant polymers (PLLA and Eudragit S100) on the nanoparticles morphology, encapsulation efficiency and curcumin recovery (defined as the lost of curcumin during the encapsulation process) were evaluated. The addition of curcumin above 3%weight led to low recovery values but there was no effect on the encapsulation efficiency. The use of soybean lecithin a biocompatible surfactant led to encapsulation efficiencies higher than when sodium lauryl sulfate was used. Similarly, the curcumin recovery decreased when Eudragit S100 were used probably due to the low interaction between the polar groups of methacrylic acid and curcumin. Infrared spectroscopy and differencial scanning calorimetry strongly suggested that curcumin was encapsulated within the nanoparticles and is dispersed in the polymer matrix in as amorphous state. Results demonstrated that miniemulsification/solvent evaporation is a robust technique to obtain nanoparticles containing curcumin since high encapsulation efficiencies were achieved for different experimental conditions.